Autogenous Bone and Bioactive Glass around Implants Placed Simultaneously with Ridge Splitting for the Treatment of Horizontal Bony Defects: A Randomised Clinical Trial - Walid Elamrousy; Mohamed Osama; Dalia Rasheed Issa (Hindawi Limited, 2021)
Objective. To compare using autogenous bone with or without bioactive glass in ridge splitting of horizontal bone defects combined with simultaneous implant placement. Materials and Methods. In control group, bone expansion was performed and autogenous bone was used to augment the intercortical bone defect. In study group, autogenous bone was mixed with bioactive glass (1 : 1 in volume). In both groups, the implants were inserted simultaneously with ridge splitting. Six months following implant insertion, bone width and height were evaluated. Statistical analysis utilizing paired Student's t-test was used for comparing results within the same group, whereas independent samples t-test was used for intergroup variables comparison. Results. The mean bone width and labial and mesiodistal crestal bone height values were increased significantly in both groups from baseline to 6 months postoperatively. Comparing the two groups showed nonstatistical significant difference regarding the labial crestal bone loss, while the ridge width gain values were significantly higher in the study group than in the control group. The mesiodistal bone loss was significantly higher in control group than in study group. Conclusion. Autogenous bone was mixed with bioactive glass (1 : 1 in volume) to fill intercortical defect created after ridge splitting to decrease peri-implant bone resorption associated with autogenous bone alone. This trial is registered with clinical trial registration: NCT04814160.